Understanding Current Procedural Terminology and HCPCS Coding Systems - 2020, 7th Edition - Mary Jo Bowie (Cengage Learning, 2020)
Master today's most current 2020 CPT® and HCPCS diagnostic and procedural coding as well as the other precise guidelines established by federal agencies, Medicare and the American Medical Association (AMA) with the most trusted source available -- Bowie's UNDERSTANDING CURRENT PROCEDURAL TERMINOLOGY AND HCPCS CODING SYSTEMS, 2020 EDITION. Updated every year to reflect the most current code sets and developments in the field, this edition integrates new case studies and new coding assignments drawn from actual professional experiences. Carefully illustrated procedures and current, interesting examples help you perfect procedural coding skills for all medical specialties and prepare you for today's certification exams. In addition, extensive hands-on practice with MindTap's new digital learning tools help you further prepare for procedural coding success.